2021
DOI: 10.3389/fpls.2021.685654
|View full text |Cite
|
Sign up to set email alerts
|

MrMYB6 From Chinese Bayberry (Myrica rubra) Negatively Regulates Anthocyanin and Proanthocyanidin Accumulation

Abstract: Anthocyanins and proanthocyanidins (PAs) are important flavonoids in Chinese bayberry (Morella rubra), which functions in fruit color and exhibits multiple health promoting and disease-preventing effects. To investigate the regulation of their biosynthesis in Chinese bayberries, we isolated and identified a subgroup 4 MYB transcription factor (TF), MrMYB6, and found MrMYB6 shared similar repressor domains with other MYB co-repressors of anthocyanin and PA biosynthesis after sequence analysis. Gene expression r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Previous studies indicated that AtMYB114 , PyMYB114 , and MdMYB114 were active regulators of anthocyanin biosynthesis in Arabidopsis ( Gonzalez et al, 2008 ), pear ( Yao et al, 2017 ), and apple ( Jiang et al, 2021 ). Other studies suggested that MdMYB12 and MrMYB6 negatively regulate anthocyanin accumulation in apple ( Mao et al, 2021 ) and Chinese bayberry ( Shi et al, 2021 ). Here, our degradome analysis showed that FamiRNA828a and FamiRNA858_R-2 targeted FaMYB114 and FaMYB308 , respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies indicated that AtMYB114 , PyMYB114 , and MdMYB114 were active regulators of anthocyanin biosynthesis in Arabidopsis ( Gonzalez et al, 2008 ), pear ( Yao et al, 2017 ), and apple ( Jiang et al, 2021 ). Other studies suggested that MdMYB12 and MrMYB6 negatively regulate anthocyanin accumulation in apple ( Mao et al, 2021 ) and Chinese bayberry ( Shi et al, 2021 ). Here, our degradome analysis showed that FamiRNA828a and FamiRNA858_R-2 targeted FaMYB114 and FaMYB308 , respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, other SG4-like also have an inhibitory effect on anthocyanin and PA bio-synthesis. For example, MrMYB6 might negatively regulate anthocyanin and PA ac-cumulation in Chinese bayberry [ 41 ]. A similar finding was observed when PtrMYB57 was overexpressed in poplar [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen of these were significantly down-regulated and differentially accumulated in BDK ( Table 1 ). Proanthocyanidins usually have astringent tastes ( Shi et al, 2021 ), and differences in the types and contents of these compounds will thus affect the fruit flavor. We found that the contents of procyanidin A2 and procyanidin C1 in BDK were lower than in DK.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoid secondary metabolites contribute to both the development and quality of plants ( Winkel-Shirley, 2001 ), with anthocyanins and proanthocyanidins forming the major flavonoid classes present in fruit ( Saito et al, 2013 ; Sakaguchi et al, 2008 ). Anthocyanins contribute to fruit color, including orange, red, pink, or blue colors, while proanthocyanidins are responsible for flavor and astringency ( Shi et al, 2021 ). Both classes represent good sources of natural antioxidants that have a role in reducing cardiovascular disease and assist with the treatment of diabetes ( Bao et al, 2005 ; Middleton, Kandaswami & Theoharides, 2000 ; Shi et al, 2018a ; Sun et al, 2012a ; Sun et al, 2012b ; Zhang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%